Rediscovering Political Economy - Postell, Joseph; Watson, Bradley C. S. (Lexington Books, 2011)
The recent economic crisis in the United States has highlighted a crisis of understanding. In this volume, Bradley C. S. Watson and Joseph Postell bring together some of America's most eminent thinkers on political economy—an increasingly overlooked field wherein political ideas and economic theories mutually inform each other. Only through a restoration of political economy can we reconnect economics to the human good. Economics as a discipline deals with the production and distribution of goods and services. Yet the study of economics can-indeed must—be employed in our striving for the best possible political order and way of life. Economic thinkers and political actors need once again to consider how the Constitution and basic principles of our government might give direction and discipline to our thinking about economic theories, and to the economic policies we choose to implement. The contributors are experts in economic history, and the history of economic ideas. They address basic themes of political economy, theoretical and practical: from the relationship between natural law and economics, to how our Founding Fathers approached economics, to questions of banking and monetary policy. Their insights will serve as trusty guides to future generations, as well as to our own.